Hypertension urgencies in the SPYRAL HTN-OFF MED Pivotal trial - Weber, Michael A.; Schmieder, Roland; Kandzari, David E.; Townsend, Raymond R.; Mahfoud, Felix; Tsioufis, Konstantinos; Kario, Kazuomi; Pocock, Stuart; Tatakis, Fotis; Ewen, Sebastian; Choi, James W.; East, Cara; et al. (Clinical Research in Cardiology, 2022)
The SPYRAL HTN-OFF MED Pivotal trial (https://clinicaltrials.gov/ct2/show/NCT02439749) demonstrated significant reductions in blood pressure (BP) after renal denervation (RDN) compared to sham control in the absence of anti-hypertensive medications. Prior to the 3-month primary endpoint, medications were immediately reinstated for patients who met escape criteria defined as office systolic BP (SBP) >= 180 mmHg or other safety concerns. Our objective was to compare the rate of hypertensive urgencies in RDN vs. sham control patients. Patients were enrolled with office SBP >= 150 and < 180 mmHg, office diastolic BP (DBP) >= 90 mmHg and mean 24 h SBP >= 140 and < 170 mmHg. Patients had been required to discontinue any anti-hypertensive medications and were randomized 1:1 to RDN or sham control. In this post-hoc analysis, cumulative incidence curves with Kaplan-Meier estimates of rate of patients meeting escape criteria were generated for RDN and sham control patients. There were 16 RDN (9.6%) and 28 sham control patients (17.0%) who met escape criteria between baseline and 3 months. There was a significantly higher rate of sham control patients meeting escape criteria compared to RDN for all escape patients (p = 0.032), as well as for patients with a hypertensive urgency with office SBP >= 180 mmHg (p = 0.046). Rate of escape was similar between RDN and sham control for patients without a measured BP exceeding 180 mmHg (p = 0.32). In the SPYRAL HTN-OFF MED Pivotal trial, RDN patients were less likely to experience hypertensive urgencies that required immediate use of anti-hypertensive medications compared to sham control.
CRIS-Team WoS Importer:2022-07-29